Cubanthonomus, a new genus of Anthonomini (Coleoptera: Curculionidae: Curculioninae) from Cuba - Anderson, Robert S. (Zootaxa, 2024)
Cubanthonomus Anderson, new genus (Coleoptera: Curculionidae: Curculioninae: Anthonomini) is here described to accommodate the Cuban species Cleogonus grossulus Suffrian, which was previously placed as incertae sedis within Cleogonini. The genus is characterized by head constricted behind the eyes, globose form, compact antennal funicle of seven antennomeres, base of pronotum strongly produced posteriorly at middle, elytra with rows of punctures (striae effaced), tarsal claws with small basal tooth, profemora with two teeth, meso- and metafemora with single small tooth. Specimens have been collected in tropical semideciduous forest but no host associations are known.